Modern contraceptive availability and stockouts: a multi-country analysis of trends in supply and consumption. Issue 3 (17th January 2021) - Muhoza, Pierre; Koffi, Alain K; Anglewicz, Philip; Gichangi, Peter; Guiella, Georges; OlaOlorun, Funmilola; Omoluabi, Elizabeth; Sodani, P R; Thiongo, Mary; Akilimali, Pierre; Tsui, Amy; Radloff, Scott
Abstract: Approximately 214 million women of reproductive age lack adequate access to contraception for their family planning needs, yet patterns of contraceptive availability have seldom been examined. With growing demand for contraceptives in some areas, low contraceptive method availability and stockouts are thought to be major drivers of unmet need among women of reproductive age, though evidence for this is limited. In this research, we examined trends in stockouts, method availability and consumption of specific contraceptive methods in urban areas of four sub-Saharan African countries (Burkina Faso, Democratic Republic of Congo, Kenya and Nigeria) and India. We used representative survey data from the Performance Monitoring for Action Agile Project that were collected in quarterly intervals at service delivery points (SDP) stratified by sector (public vs private), with all countries having five to six quarters of surveys between 2017 and 2019. Among SDPs that offer family planning, we calculated the percentage offering at least one type of modern contraceptive method (MCM) for each country and quarter, and by sector. We examined trends in the percentage of SDPs with stockouts and which currently offer condoms, emergency contraception, oral pills, injectables, intrauterine devices and implants. We also examined trends of client visits for specific methods and the resulting estimated protection from pregnancy by quarter and country. Across all countries, the vast majority of SDPs had at least one type of MCM in-stock during the study period. We find that the frequency of stockouts varies by method and sector and is much more dynamic than previously thought. While the availability and distribution of long-acting reversible contraceptives (LARCs) were limited compared to other methods across countries, LARCs nonetheless consistently accounted for a larger portion of couple years of protection. We discuss findings that show the importance of engaging the private sector towards achieving global and national family planning goals.